Baina al-Kalimāt wa al-Rawā’i': Istiksyāf Uslūbī li Ṣuwar al-Balāghah fī Sūrah al-Qalam - Murtadho, Muhammad Alfa Choirul; Barnabila, Muhammad Kesit; Anshori, Mohammad; Noor, Dizhwar Aydeen (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2025)
Al-Qur’an is recognized not only as a sacred scripture containing religious teachings but also as a literary masterpiece rich in linguistic beauty and artistic imagery. Its captivating style brings vivid and meaningful visual images to life, allowing divine messages to be conveyed in a deeper and more thought-provoking manner to its readers. This study aims to analyze the use of literary imagery elements in Surah Al-Qalam and their role in effectively and aesthetically delivering religious messages. Employing a qualitative approach, the study uses descriptive analysis of the verses of Surah Al-Qalam through the lens of classical Arabic stylistics, focusing particularly on tasybīh (simile), isti‘ārah (metaphor), tashkhīṣ (personification), kināyah (irony), and majāz (metonymy). The findings reveal that these five imagery elements are harmoniously applied to express complex meanings in a visual, imaginative, and communicative manner. Tashkhīṣ animates abstract concepts; tasybīh and isti‘ārah enhance the visual representation of teachings; while kināyah and majāz deepen symbolic meaning and strengthen the rhetorical impact of the verses. The study concludes that the use of imagery in Surah Al-Qalam is not mere literary decoration but serves as a crucial instrument in clarifying and reinforcing the divine message.